Private Sector and Refugees : Pathways to Scale - The Bridgespan Group (International Finance Corporation, Washington, DC, 2019)
According to United Nations High Commissioner for Refugees (UNHCR), the United Nations Refugee Agency, by the end of 2017, nearly 70 million people worldwide were forcibly displaced - more than the entire population of the United Kingdom. Governments, aid agencies, and non-government organizations (NGOs) have long provided humanitarian aid for refugees, addressing immediate needs such as food, water, and shelter. The need for sustainable, long-term solutions that mitigate the negative impacts of forcible displacement, uplift refugees, and support host communities is therefore becoming more acute. Indeed, the development community is increasingly focusing on empowering refugees as agents of their own lives and economic contributors - from providing skills training, to offering employment, and enabling access to financial products and services. Private sector actors are inherently well-positioned to enhance and scale these efforts, given their strategic capabilities and business models. Multinational corporations like Mastercard, regional, and national businesses such as Equity Bank and PowerGen, social enterprises like NaTakallam and Sanivation, and a range of others across industries, are demonstrating the potential roles of the private sector in supporting refugees and host communities.